Bimetallic self-lubricating composite coating and preparation method thereof

By applying bimetallic self-lubricating composite coating on heavy machinery equipment, using copper alloy as the thermal carrier layer and tin-based Baptbhd alloy matrix as the lubricating friction reduction layer, combined with ultra-high-speed laser cladding technology, the Paptbhd alloy has been solved. The problems of application difficulties under high load conditions and insufficient compliance and lubrication performance of copper alloys have achieved efficient lubrication and friction reduction effects.

CN119162487BActive Publication Date: 2025-02-18XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411623075.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

In the prior art, Papt alloy is difficult to apply under high load conditions, and the compliance and lubricating performance of copper alloys are insufficient, which makes it difficult to effectively solve the friction and wear problems of heavy machinery equipment.

Method used

Bimetallic self-lubricating composite coating, including thermally conductive bearing layers and lubricating friction reducing layers, thermally conductive bearing layers use copper alloys such as tin bronze and aluminum bronze, and lubricating friction reducing layers use tin-based Babbitt alloy matrix, solid lubricant and hard The phase is prepared by ultra-high-speed laser cladding technology.

Benefits of technology

The lubrication and friction reduction effect of Papistol alloy is achieved under high load conditions, while maintaining the mechanical strength and thermal conductivity of the copper alloy, solving the problem of insufficient compliance and lubrication performance of the copper alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162487B_ABST
    Figure CN119162487B_ABST
Patent Text Reader

Abstract

The present disclosure provides a bimetallic self-lubricating composite coating and a preparation method thereof, which relates to the technical field of metal coating modification. The bimetallic self-lubricating composite coating includes: a heat-conducting bearing layer and a lubricating and anti-friction layer; wherein: the heat-conducting bearing layer includes a copper alloy, and the copper alloy includes tin bronze and / or aluminum bronze; the lubricating and anti-friction layer includes a tin-based babbitt alloy matrix, a solid lubricant, and a plurality of hard phases. The bimetallic self-lubricating composite coating provided by the present disclosure can use the copper alloy as a heat-conducting bearing layer and use the tin-based babbitt alloy matrix, the solid lubricant, and the hard phase as a lubricating and anti-friction layer, thereby maintaining the mechanical strength, hardness, thermal conductivity, and heat resistance of the copper alloy, and lubricating and anti-friction can be performed based on the babbitt alloy, thereby solving the problem in the related art that the copper alloy has insufficient compliance, poor adaptability to the bending and misalignment of the shaft and the bearing, and relatively poor lubrication performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present disclosure relate to the technical field of metal coating modification, and in particular, to a bimetallic self-lubricating composite coating and a method for preparing the bimetallic self-lubricating composite coating. Background Art

[0002] With the technological progress and scale expansion of civil fields such as wind power generation, tunnel engineering, and petrochemicals, the requirements for material performance of heavy machinery and equipment such as wind turbines, shield machines, and deep well oil drilling rigs are also increasing. The reliability and durability of key components of these equipment have become important indicators for measuring and restricting equipment performance. In the process of actual application, the damage and failure of equipment components are usually caused by a variety of reasons, one of which is friction and wear, which is the main factor affecting the service life and reliability of heavy machinery and equipment. Efficient lubrication and friction reduction measures are crucial to improving equipment stability and working life.

[0003] At present, Babbitt alloy and copper alloy are the two main metal materials used for lubrication, friction reduction and strengthening of large spindles, bearings and bushings. Among them, Babbitt alloy is widely used in steam turbines, internal combustion engines and other fields due to its excellent friction reduction, compliance and anti-seizure properties. However, due to the low mechanical properties and heat resistance of Babbitt alloy, and the centrifugal casting process commonly used to prepare Babbitt alloy coatings, there are problems such as pores and insufficient bonding strength, which makes it impossible to lubricate and reduce friction based on Babbitt alloy under high load conditions. In addition, although copper alloy has relatively high mechanical strength, hardness, thermal conductivity and heat resistance, and is more cost-effective, copper alloy has insufficient compliance, poor adaptability to bending and misalignment of shafts and bearings, and relatively poor lubrication performance. Summary of the invention

[0004] The purpose of the present disclosure is to provide a bimetallic self-lubricating composite coating and a method for preparing the bimetallic self-lubricating composite coating, thereby at least to a certain extent overcoming the problems of being unable to apply Babbitt alloy under high load conditions and the poor adaptability and lubrication performance of copper alloys due to the limitations and defects of related technologies.

[0005] According to one aspect of the present disclosure, a bimetallic self-lubricating composite coating is provided, wherein the bimetallic self-lubricating composite coating comprises a heat-conducting bearing layer and a lubricating and anti-friction layer; wherein:

[0006] The heat-conducting bearing layer comprises a copper alloy, and the copper alloy comprises tin bronze and / or aluminum bronze;

[0007] The lubricating and anti-friction layer comprises a tin-based babbitt alloy matrix, a solid lubricant and multiple hard phases.

[0008] In an exemplary embodiment of the present disclosure, the tin bronze is Cu-12Sn-2Ni, and the aluminum bronze is Cu-10Al-3Fe;

[0009] The tin-based babbitt alloy matrix includes a Sn-Sb-Cu matrix, and the Sn-Sb-Cu matrix includes at least one of Sn-4Sb-4Cu, Sn-8Sb-4Cu, Sn-8Sb-8Cu and Sn-11Sb-6Cu.

[0010] In an exemplary embodiment of the present disclosure, the solid lubricant includes one or more of silver, nickel-coated graphite, calcium fluoride, barium fluoride, lanthanum fluoride, molybdenum disulfide, and tungsten disulfide;

[0011] The hard phase is an oxide, and the oxide includes one or more of ZrO2, Y2O3, Al2O3, and Cr2O3.

[0012] In an exemplary embodiment of the present disclosure, in the lubricating and friction-reducing layer, the mass proportion of the solid lubricant is 10% to 35%, the mass proportion of the hard phase is 10% to 25%, and the mass proportion of the tin-based babbitt alloy matrix is ​​40% to 80%.

[0013] In an exemplary embodiment of the present disclosure, the particle sizes of the copper alloy and the tin-based babbitt alloy matrix are 50-100 μm, and the particle sizes of the solid lubricant and the hard phase are in the range of 15-50 μm.

[0014] According to one aspect of the present disclosure, there is provided a method for preparing a bimetallic self-lubricating composite coating according to any one of the above, comprising the following steps:

[0015] Step 1: ball-milling and mixing a tin-based babbitt alloy matrix, a solid lubricant and a hard phase powder, and drying the mixture to obtain a composite material powder including a tin-based babbitt alloy matrix;

[0016] Step 2: Grinding and cleaning the surface of the bearing steel to obtain a clean bearing steel surface matrix;

[0017] Step 3: Use ultra-high-speed laser cladding technology to clad copper alloy powder on the surface of the clean bearing steel to obtain a heat-conducting bearing layer of a bimetallic self-lubricating composite coating;

[0018] Step 4: Remove the oxide scale on the surface of the heat-conducting bearing layer, and perform secondary cladding of the composite material powder including a tin-based babbitt alloy matrix on the surface of the heat-conducting bearing layer to obtain the lubricating and friction-reducing layer of the bimetallic self-lubricating composite coating. The heat-conducting bearing layer and the lubricating and friction-reducing layer together constitute the bimetallic self-lubricating composite coating.

[0019] In an exemplary embodiment of the present disclosure, the surface hardness of the bimetallic self-lubricating composite coating is 80 to 130 HV 0.2 The room temperature friction coefficient of the bimetallic self-lubricating composite coating is 0.2 to 0.45, and the wear rate of the bimetallic self-lubricating composite coating is 1.5×10 -7 ~4×10 -7 mm 3 / N·m.

[0020] In an exemplary embodiment of the present disclosure, during the formation of the heat-conducting bearing layer, the process parameters used include at least one of the following: laser power of 3000-4000 W, scanning rate of 1500-2500 mm / min, laser overlap rate of 50%, and powder feeding rate of 10-20 g / min;

[0021] In the process of forming the lubricating and anti-friction layer, the process parameters used include at least one of the following: laser power of 1000-1500W, scanning rate of 900-1200mm / min, laser overlap rate of 50%, and powder feeding rate of 10-15g / min;

[0022] During the formation of the heat-conducting bearing layer and the lubricating and friction-reducing layer, argon is used as a protective gas and a powder feeding gas; wherein the powder feeding gas flow rate of argon is 2 to 5 L / min, and the protective gas flow rate of argon is 10 to 15 L / min.

[0023] In an exemplary embodiment of the present disclosure, in the preparation process of the composite material powder including the tin-based babbitt alloy matrix, the ball milling mixing is performed in a dry mixing manner, the ratio of the sphere to the material body consisting of the tin-based babbitt alloy matrix, the solid lubricant and the hard phase powder is 5:1, the ball milling speed is 80-200 r / min, and the ball milling time is 2-8 h;

[0024] After the ball milling is completed, the moisture in the material body is removed by vacuum drying to obtain a composite material powder including a tin-based babbitt alloy matrix; wherein, during the vacuum drying process, the temperature used is 100° C. to 120° C., and the required vacuum drying time is 2 h to 4 h.

[0025] In an exemplary embodiment of the present disclosure, the thickness of the heat-conducting bearing layer is 300-1000 μm, and the thickness of the lubricating and anti-friction layer is 500-2000 μm.

[0026] The bimetallic self-lubricating composite coating provided in the embodiments of the present disclosure, on the one hand, includes a heat-conducting bearing layer and a lubricating and anti-friction layer; and the heat-conducting bearing layer includes a copper alloy, and the copper alloy includes tin bronze and / or aluminum bronze; the lubricating and anti-friction layer includes a tin-based babbitt alloy matrix, a solid lubricant, and a plurality of hard phases; and lubrication and friction reduction based on the babbitt alloy under high load conditions is achieved; on the other hand, since the copper alloy can be used as the heat-conducting bearing layer and the tin-based babbitt alloy matrix, the solid lubricant, and the hard phase can be used as the lubricating and anti-friction layer, lubrication and friction reduction can be performed based on the babbitt alloy while maintaining the mechanical strength, hardness, thermal conductivity and heat resistance of the copper alloy, thereby solving the problem in the related art that the copper alloy has insufficient compliance, poor adaptability to bending and misalignment of the shaft and bearing, and relatively poor lubrication performance.

[0027] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.

[0029] Figure 1 A flow chart schematically illustrates a method for preparing a bimetallic self-lubricating composite coating according to an exemplary embodiment of the present disclosure.

[0030] Figure 2 A cross-sectional scanning morphology image of a bimetallic self-lubricating composite coating obtained based on Example 1 according to an exemplary embodiment of the present disclosure is schematically shown.

[0031] Figure 3 An example diagram schematically shows a cross-sectional microhardness curve test result of a bimetallic self-lubricating composite coating obtained based on Examples 1-4 according to an example embodiment of the present disclosure.

[0032] Figure 4 An example diagram schematically shows performance test results of a friction curve of a bimetallic self-lubricating composite coating obtained based on Examples 1-4 according to an example embodiment of the present disclosure.

[0033] Figure 5 An example diagram schematically shows a performance test result of the wear rate of a bimetallic self-lubricating composite coating obtained based on Examples 1-4 according to an example embodiment of the present disclosure. DETAILED DESCRIPTION

[0034] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; on the contrary, these embodiments are provided so that the present disclosure will be more comprehensive and complete, and the concepts of the example embodiments are fully conveyed to those skilled in the art. The described features, structures, or characteristics may be combined in one or more embodiments in any suitable manner. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or other methods, components, devices, steps, etc. may be adopted. In other cases, known technical solutions are not shown or described in detail to avoid obscuring various aspects of the present disclosure.

[0035] The terms "a", "an", "the" and "said" used in this specification are used to indicate the presence of one or more elements / components, etc.; the terms "including" and "having" are used to express an open-ended inclusion and mean that there may be additional elements / components, etc. in addition to the listed elements / components, etc.; the terms "first" and "second" etc. are used only as labels and are not intended to limit the quantity of their objects.

[0036] At present, Babbitt alloy and copper alloy are the two main metal materials used for lubrication, friction reduction and strengthening of large spindles, bearings and bushings. Babbitt alloy is widely used in steam turbines, internal combustion engines and other fields due to its excellent friction reduction, compliance and anti-seizure properties. However, the mechanical properties and heat resistance of Babbitt alloy are relatively low, and the centrifugal casting process commonly used to prepare Babbitt alloy coatings has problems such as pores and insufficient bonding strength, which limits the application of Babbitt alloy under high load conditions; in addition, the application of centrifugal casting process is also limited for large spindles, bearings and bushings. Although copper alloys such as aluminum bronze and tin bronze have relatively high mechanical strength, hardness, thermal conductivity and heat resistance, and are more cost-effective, they have insufficient compliance, poor adaptability to bending and misalignment of shafts and bearings, and relatively poor lubrication performance.

[0037] In some related technical solutions, copper-based alloys and tin-based babbitt alloys can be built-up onto the surface of a steel substrate by a build-up welding method. Two welding machines are used for digital control respectively, so that the two alloys are welded in a staggered current wave peak manner to produce a bushing with both metals. However, the bonding strength between babbitt alloy and steel is only 70 to 84 MPa, which is relatively low.

[0038] In other related technical solutions, a high-load-bearing babbitt alloy-based composite material can be prepared using babbitt alloy as the matrix and woven copper mesh as the reinforcement phase using traditional casting technology to solve the problems of low load-bearing capacity and poor thermal conductivity of babbitt alloy. However, the preparation process of the composite material is relatively complicated.

[0039] In some other related technical solutions, the interface strength of the Babbitt alloy coating can be effectively enhanced by heating the substrate to 40-70°C and cladding the Babbitt alloy wire in an inert gas atmosphere. However, the composition of the Babbitt alloy is not optimized, and the problem of poor mechanical properties and thermal conductivity of the Babbitt alloy cannot be solved.

[0040] Therefore, how to combine the advantages of copper alloy and babbitt alloy and optimize their components to develop a composite coating with high load-bearing capacity, strong bonding force, high compliance, high thermal conductivity and self-lubricating performance is crucial to improving the performance of large spindles, bearings and bushings. At the same time, in order to solve the limitations of existing coating preparation technology, the example embodiment of the present disclosure adopts ultra-high-speed laser cladding technology to prepare the composite coating; specifically, ultra-high-speed laser cladding technology, as an advanced surface modification technology, can form a modified coating with extremely low dilution rate and strong bonding by controlling the light-powder coupling accuracy. It has technical advantages such as high bonding strength, low heat input, fine organization, and fast processing speed, and can effectively improve the service performance of the composite coating.

[0041] Based on this, the exemplary embodiments of the present disclosure first provide a bimetallic self-lubricating composite coating; specifically, the lubricating composite coating may include a heat-conducting bearing layer and a lubricating and anti-friction layer; wherein the heat-conducting bearing layer described herein may include a copper alloy, and the copper alloy described herein includes tin bronze and / or aluminum bronze; the lubricating and anti-friction layer described herein includes a tin-based babbitt alloy matrix, a solid lubricant, and multiple hard phases.

[0042] The bimetallic self-lubricating composite coating provided in the embodiments of the present disclosure, on the one hand, includes a heat-conducting bearing layer and a lubricating and anti-friction layer; and the heat-conducting bearing layer includes a copper alloy, and the copper alloy includes tin bronze and / or aluminum bronze; the lubricating and anti-friction layer includes a tin-based babbitt alloy matrix, a solid lubricant, and a plurality of hard phases; and lubrication and friction reduction based on the babbitt alloy under high load conditions is achieved; on the other hand, since the copper alloy can be used as the heat-conducting bearing layer and the tin-based babbitt alloy matrix, the solid lubricant, and the hard phase can be used as the lubricating and anti-friction layer, lubrication and friction reduction can be performed based on the babbitt alloy while maintaining the mechanical strength, hardness, thermal conductivity and heat resistance of the copper alloy, thereby solving the problem in the related art that the copper alloy has insufficient compliance, poor adaptability to bending and misalignment of the shaft and bearing, and relatively poor lubrication performance.

[0043] Hereinafter, each component included in the bimetallic self-lubricating composite coating will be explained and illustrated in detail.

[0044] (1) Tin bronze and / or aluminum bronze in copper alloys. Specifically, the tin bronze described here is Cu-12Sn-2Ni, and the aluminum bronze is Cu-10Al-3Fe.

[0045] (2) The tin-based babbitt alloy matrix included in the lubricating and anti-friction layer. Specifically, the tin-based babbitt alloy matrix described herein may include a Sn-Sb-Cu matrix; meanwhile, the Sn-Sb-Cu matrix described herein may include Sn-4Sb-4Cu, Sn-8Sb-4Cu, Sn-8Sb-8Cu, Sn-11Sb-6Cu, and the like.

[0046] (3) Solid lubricants included in the lubricating and anti-friction layer. Specifically, the solid lubricants described herein may include silver, nickel-coated graphite, calcium fluoride, barium fluoride, lanthanum fluoride, molybdenum disulfide, tungsten disulfide, and the like.

[0047] (4) The hard phase included in the lubricating and anti-friction layer. Specifically, the hard phase described herein is an oxide, and the oxide described herein includes different oxides such as ZrO2, Y2O3, Al2O3, and Cr2O3.

[0048] At the same time, in the lubricating and friction-reducing layer, the mass proportion of the solid lubricant is 10% to 35%, the mass proportion of the hard phase is 10% to 25%, and the mass proportion of the tin-based babbitt alloy matrix is ​​40% to 80% (that is, in the lubricating and friction-reducing layer, except for the solid lubricant and the hard phase, the rest is the tin-based babbitt alloy matrix); and, the particle size of the copper alloy and the tin-based babbitt alloy matrix recorded here is 50 to 100 μm, and the particle size range of the solid lubricant and the hard phase is 15 to 50 μm.

[0049] Based on the above-mentioned contents, it can be known that the bimetallic self-lubricating composite coating described in the exemplary embodiments of the present disclosure can, on the one hand, further optimize the lubrication performance and wear resistance of the bimetallic self-lubricating composite coating to form a lubricating and anti-friction layer; on the other hand, by using a copper alloy such as tin bronze or aluminum bronze to form a heat-conducting bearing layer between the lubricating and anti-friction layer and the substrate, the heat resistance and plastic deformation resistance of the tin-based babbitt alloy during service are improved; on the other hand, by using ultra-high-speed laser cladding technology to prepare the coating with high bonding strength and low dilution rate, a bimetallic composite coating with strong bonding, high thermal conductivity, high load-bearing capacity, high compliance and self-lubricating properties is formed.

[0050] It should be noted that in the bimetallic self-lubricating composite coating formed, the heat-conducting bearing layer is at the bottom layer, and the lubricating and anti-friction layer is at the surface layer, and the bimetallic self-lubricating composite coating is formed based on the heat-conducting bearing layer and the lubricating and anti-friction layer. Under this premise, when the bimetallic self-lubricating composite coating is subjected to external friction, due to the low melting point of the babbitt alloy, the local temperature rise and melting during the friction process will cause the effective thickness of the coating to decrease and the babbitt alloy to transfer and adhere to other areas, while the copper alloy at the bottom layer can rely on the high thermal conductivity to transfer the heat brought by the friction to other locations, so that the overall temperature uniformity of the bimetallic self-lubricating composite coating is better, and the babbitt alloy at the surface layer is also less likely to melt, so that the babbitt alloy can better adapt to the high-load and high-speed service environment; at the same time, when the bimetallic self-lubricating composite coating is subjected to external friction, the good lubrication function of the lubricating and anti-friction layer can reduce the friction of the bimetallic self-lubricating composite coating, thereby solving the problem of insufficient compliance of the copper alloy, poor adaptability to the bending and misalignment of the shaft and bearing, and relatively poor lubrication performance.

[0051] It is also necessary to further explain here that the Sn-Sb-Cu based composite material of the lubricating and friction reducing layer includes a solid lubricant, a soft matrix phase Sn-Sb-Cu and a hard reinforcing phase; and the soft matrix phase Sn-Sb-Cu can withstand the impact and vibration generated during the friction process, so that the coating has better running-in properties; and the hard reinforcing phase can reduce the contact area between the bearing and the shaft during the friction process, thereby reducing the friction coefficient and wear rate, so that the coating has good wear resistance; at the same time, the concave-convex gap between the soft matrix phase Sn-Sb-Cu and the hard phase is conducive to the accumulation of solid lubricants, thereby promoting the formation of the lubricating layer, and further improving the lubricating and friction reducing properties of the obtained lubricating layer.

[0052] The exemplary embodiment of the present disclosure also provides a method for preparing a bimetallic self-lubricating composite coating. Figure 1 As shown, the preparation method of the bimetallic self-lubricating composite coating may include the following steps:

[0053] Step S110, ball-milling and mixing the tin-based babbitt alloy matrix, the solid lubricant and the hard phase powder, and drying them to obtain a composite material powder including the tin-based babbitt alloy matrix;

[0054] Step S120, grinding and cleaning the surface of the bearing steel to obtain a clean bearing steel surface matrix;

[0055] Step S130, using ultra-high-speed laser cladding technology to clad the surface of the clean bearing steel with copper alloy powder to obtain a heat-conducting bearing layer of a bimetallic self-lubricating composite coating;

[0056] Step S140, removing the oxide scale on the surface of the heat-conducting bearing layer, and performing secondary cladding of the composite material powder including a tin-based babbitt alloy matrix on the surface of the heat-conducting bearing layer to obtain a lubricating and anti-friction layer of the bimetallic self-lubricating composite coating, and the heat-conducting bearing layer and the lubricating and anti-friction layer together constitute the bimetallic self-lubricating composite coating.

[0057] The surface hardness of the bimetallic self-lubricating composite coating obtained by the above preparation method is 80-130 HV. 0.2 The room temperature friction coefficient of the bimetallic self-lubricating composite coating is 0.2-0.45, and the wear rate of the bimetallic self-lubricating composite coating is 1.5×10 -7 ~4×10 -7 mm 3 / N·m. Further, in the preparation method described above, in the process of forming the heat-conducting bearing layer, the process parameters used include at least one of the following: laser power of 3000-4000W, scanning rate of 1500-2500mm / min, laser overlap rate of 50%, powder feeding rate of 10-20g / min; in the process of forming the lubricating and anti-friction layer, the process parameters used include at least one of the following: laser power of 1000-1500W, scanning rate of 900-1200mm / min, laser overlap rate of 50%, powder feeding rate of 10-15g / min; in the process of forming the heat-conducting bearing layer and the lubricating and anti-friction layer, argon is used as the protective gas and powder feeding gas; wherein, the powder feeding gas flow rate of argon is 2-5L / min, and the protective gas flow rate of argon is 10-15L / min. Furthermore, in the preparation method described above, in the preparation process of the composite material powder including the tin-based babbitt alloy matrix, the ball milling mixing is carried out by dry mixing, the ratio of the ball to the material body composed of the tin-based babbitt alloy matrix, the solid lubricant and the hard phase powder is 5:1, the ball milling speed is 80-200r / min, and the ball milling time is 2-8h; after the ball milling is completed, the water in the material body is removed by vacuum drying to obtain the composite material powder including the tin-based babbitt alloy matrix; wherein, in the process of vacuum drying, the temperature used is 100℃~120℃, and the required vacuum drying time is 2h~4h. Finally, the thickness of the heat-conducting bearing layer obtained based on the above preparation method is 300~1000μm, and the thickness of the lubricating and anti-friction layer is 500~2000μm.

[0058] The following will further explain and illustrate the specific implementation process of the preparation method of the above-mentioned bimetallic self-lubricating composite coating. Specifically, in the specific application process, first, the Sn-Sb-Cu matrix, solid lubricant and hard phase powder are ball-milled and dried to obtain Sn-Sb-Cu based composite material powder; wherein, the ball milling mixing recorded here adopts a dry mixing form, with a ball-to-material ratio of 5:1, a ball milling speed of 80-200r / min, and a ball milling time of 2-8h; after ball milling, the vacuum drying temperature is 100℃~120℃, and the time is 2h~4h, the raw material powder is fully mixed and the moisture in the mixed powder is removed; secondly, the surface of the bearing steel is polished and cleaned to obtain a clean matrix; then, the copper alloy powder is clad on the surface of the clean bearing steel using ultra-high-speed laser cladding technology to obtain the thermal conductive bearing layer part of the bimetallic self-lubricating composite coating. ; Among them, the copper alloy and Sn-Sb-Cu matrix powders used in the ultra-high-speed laser cladding process used here have a particle size range of 50 to 100 μm, and the particle size range of the solid lubricant and the hard phase is 15 to 50 μm; at the same time, the reason for using this particle size is that if the powder particle size of the solid lubricant and the hard phase is too small, it will burn during the coating cladding preparation process, thereby affecting the lubrication effect; and, if the powder particle size is too large, it will split the matrix, causing the comprehensive mechanical properties of the material to drop significantly, and it will be more easily torn during the friction and wear process; finally, the oxide scale on the surface of the heat-conducting bearing layer is removed, and the Sn-Sb-Cu based composite material powder obtained after ball milling mixing is used for secondary cladding on the surface to obtain the lubricating and friction-reducing layer part of the bimetallic self-lubricating composite coating. It should be noted that in the process of preparing the heat-conducting bearing layer with copper alloy, the ultra-high-speed laser cladding process parameters used are: laser power of 3000-4000W, scanning rate of 1500-2500mm / min, laser overlap rate of 50%, and powder feeding rate of 10-20g / min (1-2 turns / min); in the process of preparing the lubricating and anti-friction layer with mixed powder, the ultra-high-speed laser cladding process parameters used are: laser power of 1000-1500W, scanning rate of 900-1200mm / min, laser overlap rate of 50%, and powder feeding rate of 10-1 5g / min (1-1.5 rpm); at the same time, in the process of preparing the heat-conducting bearing layer and the lubricating and anti-friction layer, argon can be used as the protective gas and the powder feeding gas; wherein the powder feeding gas flow rate of argon is 2-5L / min, and the protective gas flow rate of argon is 10-15L / min; further, the thickness of the heat-conducting bearing layer obtained by this method is 300-1000μm, and the thickness of the lubricating and anti-friction layer obtained by this method is 500-2000μm; under this premise, the composition and thickness of the obtained heat-conducting bearing layer and the lubricating and anti-friction layer can meet the use of the coating under different service conditions.

[0059] At this point, the preparation method of the bimetallic self-lubricating composite coating recorded in the exemplary embodiment of the present disclosure has been fully realized; based on the above-mentioned contents, it can be known that in the preparation process of the bimetallic self-lubricating composite coating, the ultra-high-speed laser cladding technology used has a high light-powder coupling accuracy, which ensures the high-quality preparation of the bimetallic self-lubricating composite coating, and the technology has a high degree of automation, low heat input, and low dilution rate. Therefore, the prepared bimetallic self-lubricating composite coating is free of cracks, pores and other defects, has a fine structure and has a good metallurgical bonding with the substrate, effectively improving the wear resistance of the substrate surface; at the same time, the addition of argon atmosphere effectively avoids the oxidation of the copper alloy and the mixed powder during the cladding process, and improves the bonding strength between the coating and the bearing steel substrate.

[0060] At the same time, the bimetallic self-lubricating composite coating and the method for preparing the bimetallic self-lubricating composite coating described in the exemplary embodiments of the present disclosure also have the following advantages: on the one hand, the bimetallic self-lubricating composite coating described in the exemplary embodiments of the present disclosure is composed of a heat-conducting bearing layer (copper alloy) and a lubricating and anti-friction layer (Sn-Sb-Cu based composite material) to form a bimetallic self-lubricating composite coating; at the same time, the mechanical and tribological properties of the tin-based babbitt alloy are optimized by adding solid lubricants and hard phases, the heat resistance and load-bearing problems of the babbitt alloy are solved by adding a copper alloy coating, and the problems of complex preparation and low bonding strength of the babbitt alloy coating are solved by an ultra-high-speed laser cladding method, thereby forming a bimetallic self-lubricating composite coating with strong bonding and high bearing capacity. On the other hand, the example embodiment of the present disclosure uses ultra-high-speed laser cladding technology to successively clad copper alloy and Sn-Sb-Cu based composite materials on the surface of bearing steel through coaxial powder feeding to form a bimetallic self-lubricating composite coating; compared with other surface modification technologies, the composite coating prepared by this technology has no macro defects such as pores and cracks, and forms a strong metallurgical bond with the substrate, which greatly improves the tribological properties of the substrate; on the other hand, the ultra-high-speed laser cladding technology used in the example embodiment of the present disclosure has high controllability, good technical repeatability, high processing efficiency (≥1m2 / h), less waste of energy and powder raw materials, and less pollution to the environment.

[0061] Hereinafter, the bimetallic self-lubricating composite coating and the preparation method of the bimetallic self-lubricating composite coating described in the exemplary embodiments of the present disclosure will be further explained and illustrated in combination with specific embodiments. Specifically:

[0062] Embodiment 1: The bimetallic self-lubricating composite coating material used in this embodiment, wherein the heat-conducting bearing layer and the lubricating and friction-reducing layer materials are respectively composed of the following powders in percentage by mass:

[0063] 1. Heat-conducting bearing layer:

[0064] Tin bronze (composition is 12% Sn, 2% Ni, the rest is Cu, particle size is 50-100μm).

[0065] 2. Lubricating and anti-friction layer:

[0066] ① 80% tin-based babbitt alloy Sn-Sb-Cu (composition is 4% Sb, 4% Cu, <1% Cd, the rest is Sn, particle size is 50-100μm);

[0067] ②10% solid lubricant (composition: 50% MoS2, 50% Ag, particle size: 15-50μm);

[0068] ③10% hard phase (composition is Al2O3, particle size is 15~50μm).

[0069] The preparation method applicable to the bimetallic self-lubricating composite coating material in this embodiment mainly includes the following steps:

[0070] Step 1: Mix and dry the Sn-Sb-Cu matrix, solid lubricant and hard phase powder. The mixing and drying parameters are: dry mixing, ball-to-material ratio of 5:1, rotation speed of 80 r / min, ball milling mixing time of 2 h to fully mix them. After ball milling, the vacuum drying temperature is set to 120°C for 2 h to remove moisture from the mixed powder and obtain a Sn-Sb-Cu based composite coating powder as a lubricating and friction reducing layer.

[0071] Step 2: Grind the surface of 42CrMo bearing steel in turn with 240#, 400#, and 800# sandpapers, then clean the surface with a cleaning agent, and obtain a clean substrate after drying.

[0072] Step three, use ultra-high-speed laser cladding technology to clad tin bronze on the surface of clean bearing steel to obtain the heat-conducting bearing layer of the bimetallic self-lubricating composite coating. The working conditions and process parameters of the ultra-high-speed laser cladding are as follows: a continuous-flow fiber laser is used as the laser light source, and a ring-shaped powder feeding cladding head with a spot size of Φ3mm is used to clad tin bronze under argon protection by coaxial powder feeding. The process parameters are: laser power of 3000W, scanning rate of 1500mm / min, laser overlap rate of 50%, powder feeding rate of 10g / min, powder feeding gas flow rate of 2L / min, and shielding gas flow rate of 10L / min.

[0073] Step 4: remove the oxide scale on the surface of the heat-conducting bearing layer obtained in step 3, and use Sn-Sb-Cu based composite material powder to perform secondary cladding on the surface to obtain the lubricating and friction-reducing layer of the bimetallic self-lubricating composite coating. The working conditions of the ultra-high-speed laser cladding are the same as those in step 3, and the process parameters are: laser power 1000W, scanning rate 900mm / min, laser overlap rate 50%, powder feeding rate 10g / min (1 turn / min), powder feeding gas flow rate 5L / min, and shielding gas flow rate 15L / min.

[0074] Among them, the cross-sectional scanning morphology of the bimetallic self-lubricating composite coating obtained based on Example 1 can be referred to Figure 2 At the same time, the composite coating sample was cut, ground and polished, and its macroscopic and microscopic morphology was analyzed using a scanning electron microscope to obtain the following Figure 2 The cross-sectional scanning morphology shown in FIG. Figure 2 It can be seen that a good metallurgical bond is formed between the bearing steel substrate / copper alloy / Sn-Sb-Cu based composite coating.

[0075] Comparative Example 1: In this comparative example, except for the bimetallic self-lubricating composite coating material, the preparation method and parameters are the same as those of Example 1.

[0076] 1. Heat-conducting bearing layer:

[0077] Tin bronze (composition is 12% Sn, 2% Ni, the rest is Cu, particle size is 50-100μm).

[0078] 2. Lubricating and anti-friction layer:

[0079] ① 80% tin-based babbitt alloy Sn-Sb-Cu (composition is 4% Sb, 4% Cu, <1% Cd, the rest is Sn, particle size is 50-100μm);

[0080] ②10% solid lubricant powder (component is Ag, particle size is 15-50μm);

[0081] ③10% hard phase powder (component: Al2O3, particle size: 15-50μm).

[0082] Compared with Example 1, the composition of the solid lubricant in this comparative example is changed from 50% MoS2 and 50% Ag to 100% Ag. The comparison test results show that the lubricating and anti-friction layer prepared in Comparative Example 1 has a relatively higher friction coefficient, which is related to the decrease in dispersibility caused by excessive addition of Ag and the decrease in lubrication performance caused by a large amount of loss during the cladding process. This shows that under the same addition mass, the synergistic strengthening effect of multiple lubricating phases is significantly better than that of a single lubricating phase.

[0083] Embodiment 2: The bimetallic self-lubricating composite coating material used in this embodiment, wherein the heat-conducting bearing layer and the lubricating and anti-friction layer materials are respectively composed of the following powders in percentage by mass:

[0084] 1. Heat-conducting bearing layer:

[0085] Aluminum bronze (composition is 10% Al, 3% Fe, the rest is Cu, particle size is 50-100μm).

[0086] 2. Lubricating and anti-friction layer:

[0087] ①55% tin-based babbitt alloy Sn-Sb-Cu (composition is 8% Sb, 8% Cu, <1% Cd, the rest is Sn, particle size is 50-100μm);

[0088] ②35% solid lubricant (composition is 50% BaF2·CaF2 eutectic, 50% WS2, particle size is 15~50μm);

[0089] ③10% hard phase (composition: 50% Zr2O, 50% Cr2O3, particle size: 15-50μm).

[0090] The preparation method applicable to the bimetallic self-lubricating composite coating material in this embodiment mainly includes the following steps:

[0091] Step 1: Mix and dry the Sn-Sb-Cu matrix, solid lubricant and hard phase powder. The mixing and drying parameters are: dry mixing, ball-to-material ratio of 5:1, rotation speed of 80 r / min, ball milling mixing time of 8 hours to fully mix them. After ball milling, the vacuum drying temperature is set to 110°C for 4 hours to remove moisture from the mixed powder and obtain a Sn-Sb-Cu based composite coating powder as a lubricating and friction reducing layer.

[0092] Step 2: Grind the surface of 42CrMo bearing steel in turn with 240#, 400#, and 800# sandpapers, then clean the surface with a cleaning agent, and obtain a clean substrate after drying.

[0093] Step three, use ultra-high-speed laser cladding technology to clad aluminum bronze on the surface of clean bearing steel to obtain the heat-conducting bearing layer of the bimetallic self-lubricating composite coating. The working conditions and process parameters of the ultra-high-speed laser cladding are as follows: a continuous-flow fiber laser is used as the laser light source, and a ring-shaped powder feeding cladding head with a spot size of Φ3mm is used to clad tin bronze under argon protection by coaxial powder feeding. The process parameters are: laser power of 3000W, scanning rate of 1500mm / min, laser overlap rate of 50%, powder feeding rate of 10g / min, powder feeding gas flow rate of 2L / min, and shielding gas flow rate of 10L / min.

[0094] Step 4: remove the oxide skin on the surface of the heat-conducting bearing layer obtained in step 3, and use Sn-Sb-Cu based composite material powder to perform secondary cladding on the surface to obtain the lubricating and friction-reducing layer of the bimetallic self-lubricating composite coating. The working conditions of the ultra-high-speed laser cladding are the same as those in step 3, and the process parameters are: laser power 1000W, scanning rate 900mm / min, laser overlap rate 50%, powder feeding rate 15g / min (1 turn / min), powder feeding gas flow rate 5L / min, and shielding gas flow rate 15L / min.

[0095] Comparative Example 2: In this comparative example, except for the preparation method and parameters, the bimetallic self-lubricating composite coating material is the same as that of Example 2.

[0096] The preparation method applicable to the bimetallic self-lubricating composite coating material in this embodiment mainly includes the following steps:

[0097] Step 1: Mix and dry the Sn-Sb-Cu matrix, solid lubricant and hard phase powder. The mixing and drying parameters are: dry mixing, ball-to-material ratio of 5:1, rotation speed of 80 r / min, ball milling mixing time of 8 hours to fully mix them. After ball milling, the vacuum drying temperature is set to 110°C for 4 hours to remove moisture from the mixed powder and obtain a Sn-Sb-Cu based composite coating powder as a lubricating and friction reducing layer.

[0098] Step 2: Grind the surface of 42CrMo bearing steel in turn with 240#, 400#, and 800# sandpapers, then clean the surface with a cleaning agent, and obtain a clean substrate after drying.

[0099] Step three, use ultra-high-speed laser cladding technology to clad aluminum bronze on the surface of clean bearing steel to obtain the heat-conducting bearing layer of the bimetallic self-lubricating composite coating. The working conditions and process parameters of the ultra-high-speed laser cladding are as follows: a continuous-flow fiber laser is used as the laser light source, and a ring-shaped powder feeding cladding head with a spot size of Φ3mm is used to clad tin bronze under argon protection by coaxial powder feeding. The process parameters are: laser power of 3000W, scanning rate of 1500mm / min, laser overlap rate of 50%, powder feeding rate of 10g / min, powder feeding gas flow rate of 2L / min, and shielding gas flow rate of 10L / min.

[0100] Step 4: remove the oxide skin on the surface of the heat-conducting bearing layer obtained in step 3, and use Sn-Sb-Cu based composite material powder to perform secondary cladding on the surface to obtain the lubricating and friction-reducing layer of the bimetallic self-lubricating composite coating. The working conditions of the ultra-high-speed laser cladding are the same as those in step 3, and the process parameters are: laser power 1500W, scanning rate 900mm / min, laser overlap rate 50%, powder feeding rate 15g / min (1 turn / min), powder feeding gas flow rate 5L / min, and shielding gas flow rate 15L / min.

[0101] Compared with Example 2, the laser power in the process parameters of the lubricating and anti-friction layer in this comparative example is increased from 1000W to 1500W. The comparison test results show that the friction coefficient and wear rate of the lubricating and anti-friction layer prepared in Comparative Example 2 are increased, which is caused by the mismatch between the coating composition and the laser power, and the solid lubricant in the composite powder is burned. This shows that as the content of solid lubricant in the Sn-Sb-Cu-based composite material powder increases, the process parameters of ultra-high-speed laser cladding also need to change accordingly.

[0102] Embodiment 3: The bimetallic self-lubricating composite coating material used in this embodiment, wherein the heat-conducting bearing layer and the lubricating and anti-friction layer materials are respectively composed of the following powders in percentage by mass:

[0103] 1. Heat-conducting bearing layer:

[0104] Tin bronze (composition is 12% Sn, 2% Ni, the rest is Cu, particle size is 50-100μm).

[0105] 2. Lubricating and anti-friction layer:

[0106] ①65% tin-based babbitt alloy Sn-Sb-Cu (composition is 11% Sb, 6% Cu, <1% Cd, the rest is Sn, particle size is 50-100μm);

[0107] ②10% solid lubricant (composition is 50% nickel-coated graphite, 50% WS2, particle size is 15-50μm);

[0108] ③25% hard phase (composition is 20% Y2O3, 40% Al2O3, 40% Cr2O3, particle size is 15-50μm).

[0109] The preparation method applicable to the bimetallic self-lubricating composite coating material in this embodiment mainly includes the following steps:

[0110] Step 1: Mix and dry the Sn-Sb-Cu matrix, solid lubricant and hard phase powder. The mixing and drying parameters are: dry mixing, ball-to-material ratio of 5:1, rotation speed of 120 r / min, ball milling mixing time of 4 hours to fully mix them. After ball milling, the vacuum drying temperature is set to 110°C for 3 hours to remove moisture from the mixed powder and obtain a Sn-Sb-Cu based composite coating powder as a lubricating and friction-reducing layer.

[0111] Step 2: Grind the surface of 42CrMo bearing steel in turn with 240#, 400#, and 800# sandpapers, then clean the surface with a cleaning agent, and obtain a clean substrate after drying.

[0112] Step three, use ultra-high-speed laser cladding technology to clad tin bronze on the surface of clean bearing steel to obtain the heat-conducting bearing layer of the bimetallic self-lubricating composite coating. The working conditions and process parameters of the ultra-high-speed laser cladding are as follows: a continuous-flow fiber laser is used as the laser light source, and a ring-shaped powder feeding cladding head with a spot size of Φ3mm is used to clad tin bronze under argon protection by coaxial powder feeding. The process parameters are: laser power of 3500W, scanning rate of 2000mm / min, laser overlap rate of 50%, powder feeding rate of 15g / min, powder feeding gas flow rate of 3L / min, and shielding gas flow rate of 12L / min.

[0113] Step 4: remove the oxide skin on the surface of the heat-conducting bearing layer obtained in step 3, and use Sn-Sb-Cu based composite material powder to perform secondary cladding on the surface to obtain the lubricating and friction-reducing layer of the bimetallic self-lubricating composite coating. The working conditions of the ultra-high-speed laser cladding are the same as those in step 3, and the process parameters are: laser power 1000W, scanning rate 1000mm / min, laser overlap rate 50%, powder feeding rate 15g / min (1 turn / min), powder feeding gas flow rate 5L / min, and shielding gas flow rate 15L / min.

[0114] Comparative Example 3: In this comparative example, except for the bimetallic self-lubricating composite coating material, the preparation method and parameters are the same as those of Example 3.

[0115] 1. Heat-conducting bearing layer:

[0116] Tin bronze (composition is 12% Sn, 2% Ni, the rest is Cu, particle size is 50-100μm).

[0117] 2. Lubricating and anti-friction layer:

[0118] ①75% tin-based babbitt alloy Sn-Sb-Cu (composition is 11% Sb, 6% Cu, <1% Cd, the rest is Sn, particle size is 50-100μm);

[0119] ②10% solid lubricant (composition is 50% nickel-coated graphite, 50% WS2, particle size is 15-50μm);

[0120] ③15% hard phase (composition is 20% Y2O3, 40% Al2O3, 40% Cr2O3, particle size is 15-50μm).

[0121] Compared with Example 3, the addition ratio of the hard phase in this comparative example is reduced from 25% to 15%. By comparing the test results, it is found that the wear rate of the lubricating and anti-friction layer prepared in Comparative Example 3 is improved, which is related to the decrease in the hard phase content in the Sn-Sb-Cu based composite coating powder and the decrease in the surface hardness of the coating. This shows that the surface hardness of the coating is in direct proportion to the wear rate.

[0122] Embodiment 4: The bimetallic self-lubricating composite coating material used in this embodiment, wherein the heat-conducting bearing layer and the lubricating and anti-friction layer materials are respectively composed of the following powders in percentage by mass:

[0123] 1. Heat-conducting bearing layer:

[0124] Aluminum bronze (composition is 10% Al, 3% Fe, the rest is Cu, particle size is 50-100μm).

[0125] 2. Lubricating and anti-friction layer:

[0126] ①70% tin-based babbitt alloy Sn-Sb-Cu (composition is 4% Sb, 4% Cu, <1% Cd, the rest is Sn, particle size is 50-100μm);

[0127] ②15% solid lubricant (composition: 30% Ag, 30% LaF3, 40% MoS2, particle size: 15-50μm);

[0128] ③15% hard phase (composition: Cr2O3, particle size: 15-50μm).

[0129] The preparation method applicable to the bimetallic self-lubricating composite coating material in this embodiment mainly includes the following steps:

[0130] Step 1: Mix and dry the Sn-Sb-Cu matrix, solid lubricant and hard phase powder. The mixing and drying parameters are: dry mixing, ball-to-material ratio of 5:1, rotation speed of 160 r / min, ball milling mixing time of 6 h to fully mix them. After ball milling, the vacuum drying temperature is set to 110°C for 3 h to remove moisture from the mixed powder and obtain a Sn-Sb-Cu based composite coating powder as a lubricating and friction reducing layer.

[0131] Step 2: Grind the surface of 42CrMo bearing steel in turn with 240#, 400#, and 800# sandpapers, then clean the surface with a cleaning agent, and obtain a clean substrate after drying.

[0132] Step three, use ultra-high-speed laser cladding technology to clad aluminum bronze on the surface of clean bearing steel to obtain the heat-conducting bearing layer of the bimetallic self-lubricating composite coating. The working conditions and process parameters of the ultra-high-speed laser cladding are as follows: a continuous-flow fiber laser is used as the laser light source, and a ring-shaped powder feeding cladding head with a spot size of Φ3mm is used to clad tin bronze under argon protection by coaxial powder feeding. The process parameters are: laser power of 4000W, scanning rate of 2500mm / min, laser overlap rate of 50%, powder feeding rate of 20g / min (2 turns / min), powder feeding gas flow rate of 5L / min, and shielding gas flow rate of 15L / min.

[0133] Step 4: remove the oxide skin on the surface of the heat-conducting bearing layer obtained in step 3, and use Sn-Sb-Cu based composite material powder to perform secondary cladding on the surface to obtain the lubricating and friction-reducing layer of the bimetallic self-lubricating composite coating. The working conditions of the ultra-high-speed laser cladding are the same as those in step 3, and the process parameters are: laser power 1100W, scanning rate 1100mm / min, laser overlap rate 50%, powder feeding rate 10g / min (1 turn / min), powder feeding gas flow rate 2L / min, and shielding gas flow rate 15L / min.

[0134] Comparative Example 4: Compared with Example 4, this comparative example does not add a heat-conducting bearing layer, and the components and preparation process of the remaining lubricating and friction-reducing layers are the same as those of Example 4.

[0135] Comparative test results show that the friction coefficient of the lubricating and anti-friction layer prepared in comparative example 4 gradually increases, and the wear rate also increases significantly. This is related to the heat generated during the friction of the coating, which causes the tin-based composite coating to heat up and deform. This shows that the addition of the heat-conducting bearing layer can significantly improve the heat resistance of the lubricating and anti-friction layer, so that it can perform its performance more stably.

[0136] Figure 3 The cross-sectional microhardness curve test results of the bimetallic self-lubricating composite coating obtained in Examples 1-4 are schematically shown; Figure 3 The test results shown show that the cross-sectional microhardness of the composite coating is tested by a HV-1000 microhardness tester. The points are taken from the top of the cross-sectional area of ​​the cladding coating to the substrate at an interval of 100 μm. The loading load is set to 200 g and the holding time is 10 s. At the same time, the hardness curve shows that the microhardness of the Sn-Sb-Cu based composite coating is about 80 to 130 HV 0.2 The microhardness is directly proportional to the content of hard phase. The microhardness of copper alloy is about 160~210HV. 0.2 .

[0137] Figure 4 The performance test results of the friction curves of the bimetallic self-lubricating composite coating obtained in Examples 1-4 are schematically shown. The tribological performance test of the composite coating is carried out in the form of ball milling friction using an MFT-4000 reciprocating friction and wear tester. The friction pair uses Si3N4 ceramic balls with a diameter of Φ6mm, a loading load of 20N, a reciprocating frequency of 5Hz, a friction length of 4mm, and a wear time of 30min. From the test results, it can be seen that the average friction coefficient of the bimetallic self-lubricating composite coating is about 0.2 to 0.45, and decreases as the lubricating phase content of the lubricating and anti-friction layer increases.

[0138] Figure 5 The performance test results of the wear rate of the bimetallic self-lubricating composite coating obtained in Examples 1-4 are schematically shown. The wear rate of the composite coating is 1.5×10-7 ~4×10 -7 mm 3 / N·m, the addition of hard phase and solid lubricant can effectively improve the tribological properties of the coating.

[0139] In order to facilitate the understanding of the present invention, the present invention is described more comprehensively and meticulously in conjunction with preferred embodiments above, but the protection scope of the present invention is not limited to the above specific embodiments.

[0140] Unless otherwise defined, all the professional terms used above have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0141] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0142] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to the exemplary embodiments of the present disclosure, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.

[0143] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any modification, use or adaptation of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.

[0144] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.

Claims

1. A bimetallic self-lubricating composite coating, characterized in that: The bimetallic self-lubricating composite coating is composed of a heat-conducting bearing layer and a lubricating and anti-friction layer; the heat-conducting bearing layer is placed at the bottom of the lubricating and anti-friction layer; wherein: The heat-conducting bearing layer is tin bronze or aluminum bronze; the tin bronze is Cu-12Sn-2Ni, and the aluminum bronze is Cu-10Al-3Fe; The lubricating and anti-friction layer is composed of a tin-based babbitt alloy matrix, a solid lubricant and a hard phase; the tin-based babbitt alloy matrix is ​​a Sn-Sb-Cu matrix, and the Sn-Sb-Cu matrix is ​​selected from any one of Sn-4Sb-4Cu, Sn-8Sb-4Cu, Sn-8Sb-8Cu and Sn-11Sb-6Cu; The solid lubricant is selected from a plurality of the group consisting of silver, nickel-coated graphite, calcium fluoride, barium fluoride, lanthanum fluoride, molybdenum disulfide and tungsten disulfide; The hard phase is an oxide, and the oxide is selected from one or more of ZrO2, Y2O3, Al2O3, and Cr2O3; In the lubricating and anti-friction layer, the mass proportion of the solid lubricant is 10% to 35%, the mass proportion of the hard phase is 10% to 25%, and the mass proportion of the tin-based babbitt alloy matrix is ​​40% to 80%.

2. The bimetallic self-lubricating composite coating according to claim 1, characterized in that: The particle size of the tin bronze, aluminum bronze and tin-based babbitt alloy matrix is ​​50-100 μm, the particle size of the solid lubricant is 15-50 μm, and the particle size of the hard phase is 15-50 μm.

3. A method for preparing a bimetallic self-lubricating composite coating according to any one of claims 1 or 2, characterized in that: The following steps are involved: Step 1: ball-milling and mixing a tin-based babbitt alloy matrix, a solid lubricant and a hard phase powder, and drying the mixture to obtain a composite material powder including a tin-based babbitt alloy matrix; Step 2: Grinding and cleaning the surface of the bearing steel to obtain a clean bearing steel surface matrix; Step 3: Using laser cladding technology to clad copper alloy powder on the surface of clean bearing steel to obtain a heat-conducting bearing layer of a bimetallic self-lubricating composite coating; Step 4: remove the oxide scale on the surface of the heat-conducting bearing layer, and perform secondary cladding of the composite material powder including a tin-based babbitt alloy matrix on the surface of the heat-conducting bearing layer to obtain a lubricating and anti-friction layer of the bimetallic self-lubricating composite coating, and the heat-conducting bearing layer and the lubricating and anti-friction layer together constitute the bimetallic self-lubricating composite coating; wherein, in the process of forming the lubricating and anti-friction layer, the laser power used is 1000-1100W.

4. The method for preparing the bimetallic self-lubricating composite coating according to claim 3, characterized in that: The surface hardness of the bimetallic self-lubricating composite coating is 80-130 HV 0.2 The room temperature friction coefficient of the bimetallic self-lubricating composite coating is 0.2-0.45, and the wear rate of the bimetallic self-lubricating composite coating is 1.5×10 -7 ~4×10 -7 mm 3 / N·m.

5. The method for preparing a bimetallic self-lubricating composite coating according to claim 3, characterized in that: In the process of forming the heat-conducting bearing layer, the process parameters used include at least one of the following: laser power of 3000-4000W, scanning rate of 1500-2500mm / min, laser overlap rate of 50%, and powder feeding rate of 10-20g / min; In the process of forming the lubricating and anti-friction layer, the process parameters used include at least one of the following: a scanning rate of 900 to 1200 mm / min, a laser overlap rate of 50%, and a powder feeding rate of 10 to 15 g / min; During the formation of the heat-conducting bearing layer and the lubricating and friction-reducing layer, argon is used as a protective gas and a powder feeding gas; wherein the powder feeding gas flow rate of argon is 2 to 5 L / min, and the protective gas flow rate of argon is 10 to 15 L / min.

6. The method for preparing a bimetallic self-lubricating composite coating according to claim 3, characterized in that: In the preparation process of the composite material powder including the tin-based babbitt alloy matrix, the ball milling mixing is carried out in a dry mixing manner, the ratio of the ball to the material body consisting of the tin-based babbitt alloy matrix, the solid lubricant and the hard phase powder is 5:1, the ball milling speed is 80-200 r / min, and the ball milling time is 2-8 hours; After the ball milling is completed, the moisture in the material body is removed by vacuum drying to obtain a composite material powder including a tin-based babbitt alloy matrix; wherein, during the vacuum drying process, the temperature used is 100° C. to 120° C., and the required vacuum drying time is 2 h to 4 h.

7. The method for preparing a bimetallic self-lubricating composite coating according to claim 3, characterized in that: The thickness of the heat-conducting bearing layer is 300-1000 μm, and the thickness of the lubricating and anti-friction layer is 500-2000 μm.

Citation Information

Patent Citations

  • Preparation process of tin-based babbitt alloy coating material on basis of 3D printing technique

    CN108866542A

  • Laser cladding composite material, laser cladding equipment and preparation method of laser cladding composite material

    CN115747792A

  • Sliding bearing

    JP1998037962A